Combining drug salt formation with amorphous solid dispersions – a double edged sword - Hiew, Tze Ning; Taylor, Lynne S. (Journal of controlled release, 2022)
Glass transition temperature (Tg) is important for amorphous compounds because it can have implications on their physical and chemical stability. With drugs that possess ionizable acidic or basic groups, salt formation is a potential strategy to reduce re-crystallization tendency through Tg elevation. While salt formation has been reported to impact re-crystallization tendency, it is not known if this holds true for all drugs and if it is useful in the context of amorphous solid dispersion (ASD) formulations. In addition, little information on the impact of salt formation on drug release performance of ASD is available. Herein, the influence of salt formation and Tg elevation on the release performance of lumefantrine (Tg = 19.7 °C) when formulated as an ASD with copovidone (PVPVA) was examined. Lumefantrine salts and lumefantrine salt–PVPVA ASDs with drug loadings (DLs) ranging from 5 to 30% were prepared. The acids used for salt formation were benzoic acid, benzenesulfonic acid, camphorsulfonic acid, hydrochloric acid, p-toluenesulfonic acid, poly(ethylene) glycol 250 diacid (PEG 250 diacid), and sulfuric acid. Salt formation resulted in an elevation of Tg compared to lumefantrine free base, with the largest increase in Tg observed with lumefantrine sulfate. With a lower Tg salt, ASDs could be formulated at higher DLs while ensuring drug release. In contrast, drug release ceased at a DL as low as 5% when Tg of the salt was high. However, ASDs with lower Tgs such as the benzoate and PEG 250 diacid salts showed poor stability against re-crystallization when stored under stress storage conditions. When using a salt in an ASD formulation, attention should be paid to the Tg of the salt, since it may show opposing effects on physical stability and drug release, at least for PVPVA-based ASDs. [Display omitted]